The Choice of Larson’s Translation Strategies and the Resulted Quality of Indonesian Translation of Hyperboles in The Shrunken Head Novel - Oktaviani, Ratih; Mujiyanto, Januarius; Saleh, Mursid (Universitas Negeri Semarang, 2018)
In translating hyperboles, the effect of exaggerating something from the source text when translated literally into the target text can cause a strange meaning and less acceptable because the terms are not in accordance with the rules of the target language. This study aimed to analyze the translation strategies used by the translator in translating type of hyperboles and its translation quality in The Shrunken Head Novel. The descriptive qualitative research approach is used as a research design. The results of the study showed that there are two types of hyperboles found in this novel, namely overstatement of numbers and quantity and impossible description. Then, there are three strategies that used by translator to translated types of hyperbole in this novel, namely the sense of the word may be translated non-figuratively, retaining the word in the original but to add the sense of the word and substituting a figurative expression from SL to TL. The analysis on translation quality showed that 212 data of hyperboles (88%) considered as accurate, 207 data (86%) belongs to acceptable and 164 data (68%) are considered as high readability.